Metal complexes of crosslinked chitosans. part II. an investigation of their hydrolysis to chitooligosaccharides using chitosanase - Trimukhe, K. D.; Bachate, S.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2007)
This paper investigates the behavior of crosslinked chitosans and metal-complexed crosslinked chitosans under similar hydrolytic conditions. Crosslinked chitosans with trimellitic anhydride, diisocyanatohexane, and dibromodecane as crosslinking agents under heterogenous reaction conditions were used as metal complexing agents by equilibrating them with metal salts such as ZnCl2, MnSO4, CuSO4, CdSO4, Pb(NO3)(2), and HgCl2. Crosslinked chitosan without metal complexation had the same hydrolytic behavior as uncrosslinked chitosan. However, when the crosslinked chitosans were complexed with metals, their rates of hydrolysis and extent of hydrolysis were significantly reduced. Thus, while for chitosan about 840 mu g/ml reducing sugar was produced in 4 h time, and 780 mu g/ml was produced for diisocyanatohexane crosslinked chitosan, only 400 mu g/ml and 320 [mu g/ml reducing sugars were produced for cadmium sulfate with crosslinked chitosan and diisocyanatohexane crosslinked chitosan, respectively. Similar results are obtained for other crosslinking agents. Studies on preincubation of the metal with the enzyme show that of the metals studied, Mn has no effect on preincubatioin with the enzyme, Hg, Cd, Pb, and Cu completely deactivates the enzyme, while Zn reduces the enzyme activity by about 43.3%. Preincubation of the metal salts with the chitosan shows that Hg and Cu completely deactivate the molecule from enzyme hydrolysis, Cd and Zn inactivate it to the extent of 56.8% and 43.3%, respectively, while Mn has no effect. Availability of the amino functions seems to be a key feature for the chitosanase to hydrolyze the chitosan polymer. This was also proved by the significant increase in the extent of hydrolysis for chitosan samples with 88% (final value 1120 mu g/ml reducing sugar) and 85% deacetylation (final value 840 mu g/ml reducing sugar). HPIC studies of the products show that a variety of oligomers are produced in the chitosanase enzyme hydrolytic reaction. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: chitooligosaccharides; Chitosan; chitosanase hydrolysis; Crosslinked chitosan; metal-complexed crosslinked chitosan

Morphological study of heavy metal complexes of chitosan and crosslinked chitosans by SEM and WAXRD - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2008)
Metal complexes of salts of Hg, Cu, Cd, Pb, Zn, and Mn with chitosan and crosslinked chitosans were prepared, and their morphologies were studied using scanning electron microscopy and wide angle X-ray diffraction. The metal ions which were specifically and strongly complexed to the amino functions of chitosans, like Hg, showed smooth surface morphology inspite of large number of ions complexed (372 mg/g of chitosan). The presence of metal ions on the surface of the chitosans could be detected with decrease in metal ion binding, in the following sequence Hg > Cu > Cd > Zn > Pb > Mn. Particularly in the case of Pb ions, the presence of these ions is clearly seen on the surface of the polymer by SEM. The number of ions of Mn complexed on the polymers was too few (5 mg/g of chitosan) to be visible. SEM of Hg and Cu complexes do not show the ``holes'' observed in the crosslinked polymers as they bind specifically to amino groups of chitosan, but for Cd, Zn, Mn, and Pb complexes, these ``holes'' are clearly visible. These results are also in agreement with the morphologies studied by WAXRD. The metal complexation data for each of these metal ions was also in the same sequence. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; metal complex; Morphology; SEM; WAXRD

Metal complexes of crosslinked chitosans: correlations between metal ion complexation values and thermal properties - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2009)
A series of heavy metal complexes of crosslinked chitosans were evaluated by thermogravimetric studies. The metal complexes with Cu, Cd and Hg ions exhibiting the highest complexing ability to chitosans (Hg 354-364, Cu 100-112, and Cd 121-160, in mg/g chitosan), had the lowest onset of degradation temperatures (range 194-210 degrees C) and the lowest final degradation temperatures (generally less than 294-304 degrees C for Hg, 296-338 degrees C for Cu, and 305-368 degrees C for Cd complexes). Mn ion, with the lowest binding to chitosans (Mn 5-7 mg/g), showed the reverse behavior, having onset (240-248 degrees C) and final degradation temperatures (range 300-368 degrees C). Zn (binding 74-87 mg/g) and Pb (binding 39-62 mg/g) ions have a binding ability intermediate to Cu/Cd/Hg and Mn extremes, and therefore the effects on onset and final degradation temperatures are intermediate to these values. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; Degradation temperature; Metal complexes; Thermal properties; Thermogravimetry